Why Consumers Prefer Green Friariello Pepper: Changes in the Protein and Metabolite Profiles Along the Ripening - Tartaglia, Maria; Sciarrillo, Rosaria; Zuzolo, Daniela; Amoresano, Angela; Illiano, Anna; Pinto, Gabriella; Jorrín-Novo, Jesús V.; Guarino, Carmine (Frontiers in Plant Science, 2021)
Fruit ripening is a physiologically complex process altering texture, color, flavor, nutritional value and aroma. However, some fruits are consumed at an early stage of ripening due to the very peculiar characteristics varying during ripening. An example is a particular ecotype of pepper, the Friariello pepper, among the most important representatives of Campania (Southern Italy) agro-alimentary culture. In this study, for the first time, the physiological variations during Friariello ripening (green, veraison and fully ripe) were evaluated by hyphenated mass spectrometric techniques in a proteomic and metabolomic approach. We found that Lutein and Thaumatin are particularly abundant in the green Friariello. Friariello at an early stage of ripening, is rich in volatile compounds like butanol, 1 3 5-cycloheptatriene, dimethyleptene, α-pinene, furan-2-penthyl, hetyl-hexanol, 3-carene, detected by GC-MS analysis, which give it the peculiar fresh and pleasant taste. The detected features of Friariello may justify its preferential consumption in the early ripening stage and outline new knowledge aimed at preserving specific agro-cultural heritage.